A High Aggression Strategy for Smaller Males - Svensson PA; Lehtonen TK; Wong BBM (PUBLIC LIBRARY SCIENCE, 2022)
Male-male conflict is common among animals, but questions remain as to when, how and by whom aggression should be initiated. Factors that affect agonistic strategies include residency, the value of the contested resource and the fighting ability of the two contestants. We quantified initiation of aggression in a fish, the desert goby, Chlamydogobius eremius, by exposing nest-holding males to a male intruder. The perceived value of the resource ( the nest) was manipulated by exposing half of the residents to sexually receptive females for two days before the trial. Resident male aggression, however, was unaffected by perceived mating opportunities. It was also unaffected by the absolute and relative size of the intruder. Instead resident aggression was negatively related to resident male size. In particular, smaller residents attacked sooner and with greater intensity compared to larger residents. These results suggest that resident desert goby males used set, rather than conditional, strategies for initiating aggression. If intruders are more likely to flee than retaliate, small males may benefit from attacking intruders before these have had an opportunity to assess the resident and/or the resource.